Cloning, Expression, and Characterization of Prophenoloxidases from Asian Corn Borer, Ostrinia furnacalis (Gunée). (18th December 2016) - Zhang, Shasha; Hong, Fang; Song, He; Wang, Lei; Liu, Qizhi; An, Chunju
Abstract : Insect phenoloxidase (PO) belongs to the type 3 copper protein family and possesses oxidoreductase activities. PO is typically synthesized as a zymogen called prophenoloxidase (PPO) and requires the proteolytic activation to function. We here cloned full-length cDNA for 3 previously unidentified PPOs, which we named OfPPO1a, OfPPO1b, and OfPPO3, from Asian corn borer, Ostrinia furnacalis (Gunée), in addition to the previously known OfPPO2. These conceptual PPOs and OfPPO2 all contain two common copper-binding regions, two potential proteolytic activation sites, a plausible thiol-ester site, and a conserved C-terminal region but lack a secretion signal peptide sequence at the N-terminus. O. furnacalis PPOs were highly similar to other insect PPOs (42% to 79% identity) and clustered well with other lepidopteran PPOs. RT-PCR assay showed the transcripts of the 4 OfPPOs were all detected at the highest level in hemocytes and at the increased amounts after exposure to infection by bacteria and fungi. Additionally, we established an Escherichia coli ( E. coli ) expression system to produce recombinant O. furnacalis PPO proteins for future use in investigating their functions. These insights could provide valuable information for better understanding the activation and functioning mechanisms of O. furnacalis PPOs.